Evidence based processes to prevent readmissions: more is better, a ten-site observational study - Jacqueline Pugh; Lauren S. Penney; Polly H. Noël; Sean Neller; Michael Mader; Erin P. Finley; Holly J. Lanham; Luci Leykum (BMC, 2021)
Abstract Background 30-day hospital readmissions are an indicator of quality of care; hospitals are financially penalized by Medicare for high rates. Numerous care transition processes reduce readmissions in clinical trials. The objective of this study was to examine the relationship between the number of evidence-based transitional care processes used and the risk standardized readmission rate (RSRR). Methods Design: Mixed method, multi-stepped observational study. Data collection occurred 2014-2018 with data analyses completed in 2021. Setting: Ten VA hospitals, chosen for 5-year trend of improving or worsening RSRR prior to study start plus documented efforts to reduce readmissions. Participants: During five-day site visits, three observers conducted semi-structured interviews (n = 314) with staff responsible for care transition processes and observations of care transitions work (n = 105) in inpatient medicine, geriatrics, and primary care. Exposure: Frequency of use of twenty recommended care transition processes, scored 0-3. Sites' individual process scores and cumulative total scores were tested for correlation with RSRR. Outcome: best fit predicted RSRR for quarter of site visit based on the 21 months surrounding the site visits. Results Total scores: Mean 38.3 (range 24-47). No site performed all 20 processes. Two processes (pre-discharge patient education, medication reconciliation prior to discharge) were performed at all facilities. Five processes were performed at most facilities but inconsistently and the other 13 processes were more varied across facilities. Total care transition process score was correlated with RSRR (R2 = 0..61, p < 0.007). Conclusions Sites making use of more recommended care transition processes had lower RSRR. Given the variability in implementation and barriers noted by clinicians to consistently perform processes, further reduction of readmissions will likely require new strategies to facilitate implementation of these evidence-based processes, should include consideration of how to better incorporate activities into workflow, and may benefit from more consistent use of some of the more underutilized processes including patient inclusion in discharge planning and increased utilization of community supports. Although all facilities had inpatient social workers and/or dedicated case managers working on transitions, many had none or limited true bridging personnel (following the patient from inpatient to home and even providing home visits). More investment in these roles may also be needed.